2013
DOI: 10.1177/1367493513496911
|View full text |Cite
|
Sign up to set email alerts
|

Children’s knowledge and beliefs about medicines

Abstract: Minor illnesses in children are often cured at home with over the counter medicines. Even though there is a wide use of medicines among children, they rarely receive medical advice about their medications from doctors or pharmacists. The aim of this study is to evaluate children's beliefs about medicines as well as to explain what children know about medicines. A cross-sectional survey was used to collect data from four primary schools in Penang Island, Malaysia. The target population of this research was scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 11 publications
6
36
0
Order By: Relevance
“…Dawood et al . found that children <12 years of age had false beliefs about the efficacy of medicines, similar to younger adolescents in the present study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Dawood et al . found that children <12 years of age had false beliefs about the efficacy of medicines, similar to younger adolescents in the present study.…”
Section: Discussionsupporting
confidence: 76%
“…Dawood et al . also showed that 11–12‐year‐old girls were more knowledgeable about the efficacy of medicines . In contrast, Wilson et al .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, only a third of young people understood the process of tablet ingestion which agrees with a previous study where more than two thirds of young people did not know how a medicine was ingested . The young people did not have a good awareness of the correct storage of medicines which concurs with another study . This is unsurprising as young people are unlikely to be responsible for medicine storage, but may indicate they have observed poor storage practices.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The young people did not have a good awareness of the correct storage of medicines which concurs with another study. [7] This is unsurprising as young people are unlikely to be responsible for medicine storage, but may indicate they have observed poor storage practices. Less than half of the young people reported they would continue taking antibiotics once they felt better.…”
Section: Discussionmentioning
confidence: 99%